Fluid-filled breast: A unique clinical presentation of invasive micropapillary carcinoma - Megha M. Kapoor, MD; Tanya W. Moseley, MD (Radiology Case Reports, 2021)
Invasive micropapillary carcinoma is a rare variant of invasive ductal carcinoma of the breast. This variant has been described as clinically aggressive due to its high frequency of lymphovascular invasion, axillary nodal metastases, and a greater degree of loco-regional recurrence. Invasive micropapillary carcinoma can have a variety of imaging presentations, typically presenting as an irregular mass. This case report describes a unique presentation of invasive micropapillary carcinoma and illustrates the propensity of invasive micropapillary carcinoma to secrete fluid and have a lack of regional lymphadenopathy. The challenges of the accompanying diagnostic imaging-work up are discussed.